Casing the joint: Explorations by the insider‐researcher preparing for work‐based projects - Workman, Barbara (The journal of workplace learning, 2007)
Purpose: The paper aims to explore factors that impinge on the "insider-researcher" (IR) when undertaking a work-based learning project, which will result in the creation of a context analysis framework. Design/methodology/approach: A qualitative, interpretative approach with the IR as central to the research process, together with data from students work-based projects, research literature and texts, and an academic advisers' focus group. Findings: Themes of benefits and constraints identified the organisation, the clients and co-workers and the IR benefiting from work-based projects. The positionality and personal attributes of the IR may be a constraint. Of major consideration are ethical issues arising from the project process. Academics' concerns include student supervision, the impact on the IR, and factors affecting change and project processes. Research limitations/implications: A small study constrained by the researcher being central to the data and therefore introducing potential bias to the interpretation. Practical implications: The creation of a context analysis framework as a tool to assist the work-based student, the academic and the workplace in preparing to implement a work-based project. Originality/value: No similar analysis tool has been published. This can contribute significantly to the work-based curriculum. The issues that concern researchers, academic practitioners and work-based students during a work-based project have not been previously investigated. A good practice guide for projects can result from this. (Contains 1 table and 1 figure.)